1994
DOI: 10.1111/j.1528-1157.1994.tb01801.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Feline Temporal Lobe Epilepsy. III: Spontaneous Sleep and Arousal Disorders in Amygdala‐Kindled Kittens

Abstract: We report the ontogeny and persistence of sleep and arousal disorders in amygdala-kindled kittens. We also identify procedural differences that may explain discrepancies in the literature on postkindling sleep disorders. The study population consisted of 12 preadolescent kittens kindled between 2.5 and 6.5 months of age, 8 of which were followed to adulthood (> or = 1 year), and 8 unkindled implanted control animals. Sleep and seizure patterns were monitored on 12-24-h polygraphic or split-screen video recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Thus we speculate that decreased sleep‐spindle activity and the appearance of strong delta waves may be a potential cause of the reduced modulation frequency seen in this study. Several previous studies demonstrated that kindling can alter sleep patterns in cats (28–30), including a slow‐wave‐sleep insomnia (31).…”
Section: Discussionmentioning
confidence: 99%
“…Thus we speculate that decreased sleep‐spindle activity and the appearance of strong delta waves may be a potential cause of the reduced modulation frequency seen in this study. Several previous studies demonstrated that kindling can alter sleep patterns in cats (28–30), including a slow‐wave‐sleep insomnia (31).…”
Section: Discussionmentioning
confidence: 99%
“…The criteria we use to score sleep stages has been described in detail (Shouse et al, 1994) and compared with human scoring procedures. The three main differences in our criteria are use of a I-min minimum duration criterion to score onset or shift from a stable sleep or waking state, use of 1-min scoring epochs to score continuation of a stable state after onset, and methods for distinguishing depth of non-rapid eye movement (NREM) sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of disruptive, epileptiform microarousals during sleep correlated with sleep fragmentation (r = -0.68, p < 0.05). Sleep fragmentation was indexed by reduced time in stable sleep states in kindled kittens as compared to unkindled controls (Table 1) (Shouse et al, 1994). The ratio of disruptive epileptiform arousals to total arousals was the most reliable predictor of interictal sleep disruption of several factors assessed, such as history or frequency of spontaneous GTCs (r = 0.01, NS) and postictal recording delay ( r = 0.3, NS).…”
Section: Coincidence Of Microarousals Interictal Sleep Disruption Amentioning
confidence: 99%
See 1 more Smart Citation